2004
DOI: 10.1152/ajpendo.00453.2003
|View full text |Cite
|
Sign up to set email alerts
|

Preserved direct hepatic insulin action in rats with diet-induced hepatic steatosis

Abstract: Recent in vivo studies have demonstrated a strong negative correlation between liver triglyceride content and hepatic insulin sensitivity, but a causal relationship remains to be established. We therefore have examined parameters of direct hepatic insulin action on isolated steatotic livers from high-fat (HF)-fed rats compared with standard chow (SC)-fed controls. Direct hepatic action of insulin was assayed in Wistar rats after 6 wk of HF diet by measuring the insulin-induced suppression of epinephrine-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…As described previously, hepatic steatosis was induced by the HF-L diet (Buettner et al 2004). Histologic examination of the liver did not reveal signs of inflammation or distinct fibrotic changes.…”
Section: Discussionmentioning
confidence: 58%
“…As described previously, hepatic steatosis was induced by the HF-L diet (Buettner et al 2004). Histologic examination of the liver did not reveal signs of inflammation or distinct fibrotic changes.…”
Section: Discussionmentioning
confidence: 58%
“…Isotopes and samples analyses. Sodium acetate-1- 13 C, potassium hexadecanoate-1,2,3,4-13 C 4 , and glyceryl tri(hexadecanoate-d 31 ) were purchased from Cambridge Isotope Laboratories (Andover, MA) and from Isotec (Miamisburg, and was served at breakfast and lunch for the meal-feeding regimen and infused duodenally for the continuous-feeding regimen.…”
Section: Methodsmentioning
confidence: 99%
“…Isotopic purity was Ͼ98% for all isotopes, and intravenous isotopes were administered as previously described (2). For all subjects, sodium acetate-1- 13 C was given at a dose of 10 g over a 24-h period starting with dinner the night before the study (Fig. 1).…”
Section: Diabetes Vol 54 September 2005mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have favored the concept that the accumulation of intra-hepatic lipids precedes the state of insulin resistance, while others have shown that hepatic TGs themselves are not toxic and may in fact protect the liver from lipotoxicity by buffering the accumulation of deleterious fatty acids (5)(6)(7)(8). Such findings suggest that hepatic steatosis is not necessarily associated with insulin resistance (9)(10)(11). In agreement with this concept, an identified population of obese humans can stay free of insulin resistance and are metabolically healthy despite morbid obesity (12).…”
Section: Introductionmentioning
confidence: 99%